Fonem Segmental Bahasa Namblong dan Distribusinya - Erniati Erniati (Balai Bahasa Provinsi Papua, 2019)
The Namblong language a Trans Newguinea language. The Namblong is spokenby approximately 4.747 people in three district in Jayapura regency. They are Namblong district, Nimboran district, and Nimbokrang district. The method uses descriptive method which consists of listen and speak technique. The data then transcribed by phonetic. The Namblong language has twenty five segmental phoneme where twenty of consonantand five vowel.